Race and the Canadian Media - Wilkes, Rima (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this assignment you will learn how to analyze newspaper articles and how to make an argument about media coverage of a specific topic of your choice. In doing so, you will gain experience conducting original research. Following the book Discourses of Domination we will focus on the role of the media in shaping issues of race/ethnicity in Canadian society.